Manajemen Hemodialisis pada Pasien Gagal Ginjal Kronik Stadium V dengan Kehamilan Trimester Pertama: Studi Kasus - Purbasari, Alfina Fitri; Triyanto, Arifin; Sukardi, Sukardi (PSIK FKKMK UGM, 2025)
Background: Chronic kidney disease in pregnancy is a medical disorder that can increase the mother and her fetal morbidity as well as mortality. The high risk of morbidity and mortality in pregnant woman undergoing hemodialysis requires the role of nurses as direct caregivers to patients.Objective: To determine the management of pregnant woman with chronic kidney disease undergoing hemodialysis.Case report: A patient, 30 years old G4P1A2 had undergone routine hemodialysis since 2018. The patient was currently pregnant with a gestational age of 7 weeks and there was an increase in the frequency of hemodialysis after her pregnancy was discovered. The patient started hemodialysis 3 times a week with a duration of 4,5 hours. The left femoral was used as dialysis access.Outcomes: After undergoing hemodialysis 3 times a week, the patient had an interdialysis weight gain of 1,3 to 2,8 kg, with a HD prescription of blood flow rate (QB) of 180-200 ml/min, QD of 500 ml/min, total fluid withdrawal (UF goal) of 2.000-3.500 ml, mini/free heparin dose and Kt/V achievement of 1,33 to 1,67 points. The patient said she felt lighter and more comfortable after undergoing hemodialysis frequency of 3 times a week.Conclusion: Interventions that need to be carried out on pregnant woman undergoing hemodialysis are dialysis intensification with increased hemodialysis frequency, UF adjusted to interdialysis weight gain, minimal use of heparin, and maternal nutritional support as the principles in supporting this high-risk pregnancy.INTISARILatar belakang: Penyakit ginjal kronis pada kehamilan adalah suatu kelainan medis yang dapat meningkatkan morbiditas dan mortalitas ibu dan janin. Dengan adanya risiko tinggi morbiditas dan mortalitas pada ibu hamil yang menjalani hemodialisis, maka dibutuhkan peran perawat sebagai pemberi asuhan langsung pada pasien.Tujuan: Mengetahui penatalaksanaan ibu hamil dengan penyakit ginjal kronis yang menjalani hemodialisis.Laporan kasus: Seorang pasien berusia 30 tahun G4P1A2 sudah menjalani hemodialisis rutin sejak tahun 2018. Pasien saat ini sedang hamil dengan usia kehamilan jalan 7 minggu dan terdapat peningkatan frekuensi hemodialisis setelah diketahui sedang hamil. Pasien mulai melakukan hemodialisis 3 kali seminggu dengan durasi 4,5 jam. Akses dialisis yang digunakan adalah femoral sinistra.Hasil: Setelah menjalani hemodialisis 3 kali seminggu, pasien mengalami kenaikan berat badan interdialisis 1,3-2,8 kg, dengan resep HD kecepatan aliran darah (QB) 180-200 ml/menit, QD 500 ml/menit, jumlah total penarikan cairan (UF goal) 2.000-3.500 ml, dosis heparin mini/ free dan capaian Kt/V 1,33-1,67. Pasien mengatakan merasa lebih ringan dan nyaman setelah menjalani hemodialisis dengan frekuensi 3 kali seminggu.Simpulan: Intervensi yang perlu dilakukan pada ibu hamil yang menjalani hemodialisis, yaitu intensifikasi dialisis dengan peningkatan frekuensi hemodialisis, UF yang disesuaikan dengan peningkatan berat badan interdialisis, penggunaan heparin seminimal mungkin, dan dukungan nutrisi ibu menjadi prinsip dalam mendukung kehamilan berisiko tinggi ini.